2017
DOI: 10.1007/s10862-017-9635-5
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Mediates Increased Negative Affect and Suicidal Ideation in Childhood Attention-Deficit/Hyperactivity Disorder

Abstract: Objective Children with attention-deficit/hyperactivity disorder (ADHD) are at greater risk for suicidal ideation and suicide attempts compared to those without ADHD. Increased risk is at least partially attributable to a subset of children with ADHD and comorbid depression or disruptive behavior disorders; however, the early predictors and mechanisms driving increased risk are not well understood. Here, we investigate the contributions of two candidate mechanisms for increased suicidal ideation in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 131 publications
1
14
0
Order By: Relevance
“…Next, we sought to identify associations between suicidal thoughts and behaviors and brain morphometry, functional connectivity at rest, and functional measures during three tasks. Specifically, we examine neural correlates of processes that have been implicated with suicidal behavior in clinical and at-risk samples of youth, named reward processing (30)(31)(32)(33) with the Monetary Incentive Delay task (34), inhibitory control (35,36) with the Stop Signal Task (37), and working memory and affective processing (38)(39)(40)(41) with an emotional version of the N-back task (42). We tested for differences in these measures using a traditional null hypothesis significance test, and complemented our analyses with Equivalence testing (26) to examine whether observed effect size were large enough to be considered meaningful based on a prespecified benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we sought to identify associations between suicidal thoughts and behaviors and brain morphometry, functional connectivity at rest, and functional measures during three tasks. Specifically, we examine neural correlates of processes that have been implicated with suicidal behavior in clinical and at-risk samples of youth, named reward processing (30)(31)(32)(33) with the Monetary Incentive Delay task (34), inhibitory control (35,36) with the Stop Signal Task (37), and working memory and affective processing (38)(39)(40)(41) with an emotional version of the N-back task (42). We tested for differences in these measures using a traditional null hypothesis significance test, and complemented our analyses with Equivalence testing (26) to examine whether observed effect size were large enough to be considered meaningful based on a prespecified benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…Working memory is conceptualized as the system responsible for the maintenance and manipulation of information within short periods of time and is influential in affecting other executive functions, such as decision‐making (Braver et al, 2009; Cowan, 2008; McCabe et al, 2010; Swann et al, 2005; Xiu et al, 2018). A recent study showed that working memory was a cognitive mediator of the relationship between ADHD and suicidal ideation in children (Bauer et al, 2018). Response inhibition is the second component.…”
Section: Introductionmentioning
confidence: 99%
“…In a long-term observation, adolescents with ADHD were at a higher risk of suicidality and repeated suicide attempts in adulthood with or without a psychiatric disorder comorbidity [14,15]. Although psychological problems concurrent with ADHD, such as depressive symptoms, specific anxiety disorders, dysthymia symptoms [13,16,17], weak cognitive function [18], and family dysfunction [13], are commonly reported as being involved in the mechanisms of suicide, a pooled data analysis of suicidality and ADHD demonstrated that ADHD is an independent risk factor for suicidality [12].…”
Section: Introductionmentioning
confidence: 99%